Interchangeability of Trastuzumab biosimilars in the neoadjuvant treatment of breast cancer: A real-life study - Prestes, Ana Paula; Cambrussi, Monica Cristina; Machado Marra, Ana Claudia; Marquezini Rovel, Isabela; Bechara, Marcela; Soares Nunes, João (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Introduction: Trastuzumab (Trt) is incorporated into Brazil’s Public Health System (SUS) for the first-line treatment of HER 2 - positive breast cancer (CaM). The interchangea bility (IC) between a comparator product and a biosimilar (BS) is a controversial topic. Post-marketing studies are needed to ensure safety and efficacy in IC situations. Objec tive: To evaluate whether IC between different manufacturers of Trt BS interferes with the rate of pathological complete response (PCR) in the neoadjuvant treatment of HER 2 – positive CaM. Methods: The clinical data of patients diagnosed with CaM, HER 2 – positive, clinical stage III, between 2020 and 2022 were reviewed. These patients received neoadjuvant treatment based on chemotherapy plus Trt, via SUS at an Onco logy Hospital located in southern Brazil. Results: Between 2020 and 2022, SUS made 4 different Trt manufacturers available. one hundred thirty-eight (138) patients were eligible for analysis. Seventy eight (78) patients received only one type of Trt compound (Non-interchangeability Group – GNIC) and 60 patients received at least 2 different Trt compounds (Interchangeability Group – GCI). Both groups were clinically comparable (age, histological profile, tumor size and lymph node staging and axillary). The IC rate over time was 11%, 53%, and 33% in 2020, 2021, and 2022, respectively. The PCR was 33.33% in GNIC versus 33.33% in GCI. Both groups were comparable in terms of incidence of myelotoxicity, infusion reactions and cardiotoxicity. Conclusion: The present study demonstrated that the IC between BS of Trt did not interfere in a statistically sig nificant way in the RPC.